1999
DOI: 10.1111/j.2042-7174.1999.tb00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacists' attitudes to adverse drug reaction reporting

Abstract: Objective — A “demonstration” scheme for adverse drug reaction (ADR) reporting by United Kingdom community pharmacists began in April, 1997. The objective of this study was to investigate community pharmacists' attitudes to and knowledge of ADR reporting and the “yellow card” scheme. Method — Structured face‐to‐face interview with community pharmacists, using a prepiloted questionnaire. Setting — Randomly selected community pharmacies within one demonstration scheme area. Key findings — Almost all of the pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
35
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 6 publications
13
35
0
Order By: Relevance
“…This finding was reasonably similar to the observation made in Malaysia where about 59.3% of the participants were not aware of the availability of PV center in their country [31]. On the other hand, the figures in the present study were lower than the figures reported in Saudi Arabia (86.8%) [16], and far higher than figures reported in Holland and in UK [19,32]. In Holland only (1%) CPs were not aware of the availability of national PV Centre [19].…”
Section: Discussionsupporting
confidence: 90%
“…This finding was reasonably similar to the observation made in Malaysia where about 59.3% of the participants were not aware of the availability of PV center in their country [31]. On the other hand, the figures in the present study were lower than the figures reported in Saudi Arabia (86.8%) [16], and far higher than figures reported in Holland and in UK [19,32]. In Holland only (1%) CPs were not aware of the availability of national PV Centre [19].…”
Section: Discussionsupporting
confidence: 90%
“…Community pharmacists have been reported to show a positive attitude toward ADR reporting [17]. Although they were well aware of their role regarding ADR monitoring, reporting of ADRs by community pharmacists was reported quite low [18]. Similar findings of under-reporting of ADRs by community pharmacists were reported in the UK [19].…”
Section: Adr Monitoring Trends In Developed Countriessupporting
confidence: 74%
“…The initial draft of the survey questionnaire was developed using information from the literature about ADR reporting among healthcare professionals [19][20][21][22][23] as well as the findings of our previous qualitative study, which involved interviews with community pharmacists.…”
Section: Methodsmentioning
confidence: 99%